Teaching pragmatics: (im)politeness in an EFL classroom - Schepers, Bruna Milano (Brazilian English Language Teaching Journal, 2014)
The main purpose of this paper is to discuss theories of politeness and impoliteness and the teaching of pragmatics in an English as a Second Language (EFL) classroom. An analysis of a brief conversation taken from an American sitcom will be proposed as a tool for teaching matters of (im)politeness in class. Brown and Levinson’s theory has been among the most influential and controversial studies in this area. There are many current issues being discussed that revolve around their theory and the fact that it does not account for cultural diversity. Therefore, the insertion of this subject in the EFL classroom is extremely important in the sense that it makes students aware of the social and cultural diversity that is involved in learning English as a second language